Predicting health trajectories - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
With data going back to pre-World War II, the HRS paints a picture of how we will age . As people age, men are less likely to have physical disabilities than women, but die earlier. Those with higher socio-economic status and education levels have less physical disabilities as they grow old. Less educated single women are often the least financially prepared for retirement. Those are the main findings of the U.S. Health and Retirement Study (HRS), described as "the mother ship" of statistics on aging by Michael Hurd, Principal Senior Researcher and Director at the RAND Center for the Study of Aging in California, USA.